International Convergence of Copyright Production - Kim, Jin-Hyuk (The Review of Economics and Statistics, 2011)
The production of copyrighted materials varies widely across countries, and how it evolves over time has important policy implications. I propose a simple dynamic model of copyrights and the public domain, which predicts conditional convergence of per capita copyright production among countries. Using book and film production data for the period 1975 to 1995, I test and confirm the model's prediction that copyright-poor countries tend to grow faster than copyright-rich countries in terms of per capita copyright production.